Role of MicroRNA in the Diagnosis and Therapy of Hepatic Metastases from Colorectal Cancer - Chorti, Angeliki; Bangeas, Petros; Papavramidis, Theodossis S.; Tsoulfas, Georgios (MicroRNA, 2018)
Introduction: Colorectal cancer is one of the most common malignancies in both genders and liver metastasis appear in more than 50% of patients with colorectal cancer, worsening its morbidity and mortality rates. The existing methods for the diagnosis and prognosis of colorectal cancer seem to be insufficient to predict its aggressiveness, leading to poor outcomes for the patient. Objective: MicroRNAs are small non-coding RNAs, which interact with mRNAs in a posttranscriptional stage, and have been found to be involved in pathogenesis of cancer and its metastases. Their utility in diagnosis of colorectal liver metastasis gains ground through serum or tissue examination. Methods: Several miRNAs are related to colorectal cancer and its liver metastasis. Conclusion: Some of them have oncogenic and other tumor suppressive role in the development of colorectal liver metastasis, while many of them have been proved to be correlated with the overall survival and prognosis of patients with colorectal cancer. The aim of the present review is to give a detailed account of the different miRNAs that have been described as playing a role in hepatic metastases from colorectal cancer, emphasizing their diagnostic, prognostic and therapeutic implications.
Keywords: therapeutic implications